A comparison of four quality of life instruments in cardiac patients: SF-36, QLI, QLMI, and SEIQoL. Issue 4 (1st October 2000) - Smith, H J; Taylor, R; Mitchell, A
Abstract : BACKGROUND: With the increasing use of quality of life measures in evaluations of cardiac interventions, criteria are needed for selecting appropriate quality of life measures. An important criterion is the sensitivity of a measure for detecting clinically important changes. OBJECTIVES: To compare the sensitivity of four measures when used in a group of cardiac patients undergoing the same intervention. METHODS: The short form 36 (SF-36), the quality of life index–cardiac version (QLI), the quality of life after myocardial infarction questionnaire (QLMI), and the schedule for the evaluation of individual quality of life (SEIQoL) were used to evaluate quality of life in a group of 22 patients after myocardial infarction or coronary artery bypass graft (CABG), at the beginning of rehabilitation and six weeks later. Analysable data were obtained from 16 patients. RESULTS: A significant improvement over time was only observed for the SF-36 subscale, vitality (p < 0.05). Five of the eight SF-36 subscales and one of the four QLMI subscales showed modest sensitivity (index: > 0.2 and < 0.5), while all other subscales showed poor sensitivity (index: < 0.2). Using SEIQoL, family was most often nominated as an area of importance to quality of life (n = 13), followed by health (n = 10), leisure/hobbies (n = 8), marriage (n = 8), and work (n = 6). CONCLUSIONS: All four QOL measures used in this study were found to lack sensitivity to change. Further research is needed using other cardiac populations and interventions in order to verify these findings, with a view to developing more sensitive quality of life scales.